Proposta de controle secundário de carga e frequência com operação conjunta das estratégias centralizada e descentralizada aplicando a microrredes - Godoy, Paulo Thiago (2020)
A microgrid (MG) can operate either connected to the main grid or islanded. When the MG operates in islanded mode, the frequency control is performed through the primary and secondary control. Primary control is responsible for ensuring the stable operation of distributed generations. Secondary control is responsible for frequency and voltage adjustment. The secondary control can be achieved through centralized, distributed or decentralized strategies. The centralized control is the most applied strategy in MGs due to the facility of the control and coordination of the distributed generators. However, the reliability of centralized control strategies is influenced by the proper functioning of the controller and the communication channel. To avoid the reliability problems of the centralized control, this paper proposes a new unified secondary control strategy comprising of centralized and decentralized control, that can capable of maintaining the MG frequency regulation even during control or communication failures. A decentralized load shedding strategy is implemented to assist MR generation and load control. To verify the proposed secondary control, the European low voltage distribution network benchmark MG is implemented in Matlab/Simulink. For the simulations, three scenarios are tested: MG central controller failure, total and partial communication system failures. The experimental results have shown that the proposed secondary control can guarantee the frequency regulation, system stability and can avoid the load shedding even during failures. The proposed strategy proved capable to restore the system to normal control operation after the failures end. However, communication delays influence the response of the proposed strategy, which can cause minor disturbances when switching the operating mode.